A pH-responsive initiator for improving the mechanical properties of cement-based materials, and its preparation method and application

By using pH-responsive initiator in cement-based materials to achieve in situ polymerization and control polymerization time and structure, the problem of improving flexural resistance and reducing compressive resistance in the prior art is solved, and the mechanical properties of cement-based materials are improved.

CN119119327BActive Publication Date: 2025-04-18JIANGSU SOBUTE NEW MATERIALS CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411597518.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-04-18
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

While improving the flexural resistance of concrete, the prior art often reduces its compressive resistance, and the in-situ polymerization process is difficult to control, resulting in difficult matching of the polymerization process with the hydration process, and it is impossible to prepare polymer/cement matrix composites with adjustable and controllable properties.

Method used

Using a pH response initiator, the aqueous solution and the oil-phase solution are mixed and emulsified to form an emulsion by mixing and emulsifying the aqueous solution with an oil-phase solution under the action of an emulsification shearer, and the active initiation components are introduced through alkali-excited capsule sustained-release material during the hydration of cement-based materials, in situ polymerization is achieved, polymerization time is controlled, and the size and stacking method of polymer and hydrated products are optimized.

Benefits of technology

It effectively improves the microstructure of cement-based materials, improves its flexural resistance, and maintains compressive resistance, realizes uniform dispersion between polymer and hydrated products, and solves the problem of media phase separation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119327B_ABST
    Figure CN119119327B_ABST
Patent Text Reader

Abstract

The present invention discloses a pH-responsive initiator for improving the mechanical properties of cement-based materials, and a preparation method and application thereof, and belongs to the technical field of building material admixtures. The preparation process of the initiator is as follows: a polymer that can be hydrolyzed under alkaline conditions is used as a shell material, and the shell material is dissolved in a solvent as an oil phase solution; a water-soluble polymer aqueous solution and a coated small molecule are mixed as an aqueous phase solution; under the action of an emulsifying shearing machine, the aqueous phase solution is poured into the oil phase solution to emulsify to form an emulsion; a diluted aqueous solution of a water-soluble polymer is added to the emulsion, and emulsification is continued; heating is performed until the solvent is completely volatilized to obtain a suspension; and capsule particles are obtained by filtering and washing. The initiator of the present invention realizes the adjustable and controllable in-situ polymerization, effectively improves the microstructure of cement-based materials, and gives cement-based materials better flexural properties without reducing their compressive properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of building material admixtures, and specifically relates to a pH response initiator for improving the mechanical properties of cement-based materials, and a preparation method and application thereof. Background Art

[0002] At present, concrete toughening includes fiber toughening, polymer toughening and nanomaterial toughening, which adjust the microstructure of concrete at various scales to improve the tensile strength and fracture performance of concrete. However, these toughening methods have shortcomings: steel fiber toughening is the most widely used among fiber toughening and has an industrial application basis, but steel fibers are easy to agglomerate and do not improve the toughness of the concrete matrix; in direct addition of polymer toughening, the polymer itself affects cement hydration and is easy to form defects in concrete; in nanomaterial toughening, nanomaterials are easy to agglomerate and are difficult to apply industrially.

[0003] Common and easy-to-operate cement-polymer paste mixing methods include directly mixing cement with polymers as binders or additives, or immersing hardened cement paste in polymer solutions. This single physical addition and blending method has many disadvantages, which makes it impossible to effectively optimize the performance of modified concrete. Most experimental results show that the flexural strength of the material is significantly improved, but the compressive strength is significantly reduced after the addition and modification of the polymer. Therefore, when adding polymer solution, a high dosage will lead to slow setting, low hydration degree, and insignificant flexural strength enhancement effect; when adding polymer emulsion, the size of the organic polymer phase ranges from 10 to 500 μm, forming "macro defects" in the cement matrix, and the larger the size of the polymer phase, the more obvious its compressive strength weakening effect. Therefore, the current polymer addition method of toughening concrete seriously sacrifices the compressive strength of concrete. These shortcomings have greatly limited its widespread application in modern concrete. Achieving the improvement of concrete toughness is currently a research hotspot and difficulty at home and abroad.

[0004] In order to solve this problem, in-situ polymerization is currently considered by researchers to be a more feasible method. Small molecule monomers are added to concrete before polymerization, and polymer polymerization is initiated while cement is hydrated, thus achieving in-situ polymerization in cement-based materials. However, current in-situ polymerization processes cannot control the polymerization process, and the polymerization process is difficult to match with the hydration process, making it impossible to prepare polymer / cement-based composite materials with adjustable and controllable properties.

[0005] Therefore, how to control the polymer polymerization time so that the monomer does not polymerize before cement hydration and does not affect cement hydration, while avoiding the polymer particles being too large and forming phase separation in the cement matrix and affecting the mechanical properties of cement-based materials, has become the main direction of current research. Summary of the invention

[0006] Technical problem to be solved: In response to the above technical problems, the present invention provides a pH-responsive initiator for improving the mechanical properties of cement-based materials, and a preparation method and application thereof. The initiator realizes adjustable and controllable in-situ polymerization, effectively improves the microstructure of cement-based materials, and gives cement-based materials better flexural properties without reducing their compressive properties.

[0007] Technical solution: A method for preparing a pH-responsive initiator for improving the mechanical properties of cement-based materials, comprising the following steps:

[0008] S1. Preparation of oil phase solution: using a polymer that can be hydrolyzed under alkaline conditions as a shell material, dissolving the shell material in a solvent as an oil phase solution;

[0009] S2. Preparation of aqueous solution: mixing a water-soluble polymer aqueous solution and a coated small molecule as an aqueous solution;

[0010] S3. Under the action of an emulsifying shearing machine, the aqueous phase solution and the oil phase solution are mixed and emulsified to form an emulsion;

[0011] S4. Adding a diluted aqueous solution of a water-soluble polymer to the emulsion, and continuing emulsification;

[0012] S5. Heating the emulsion in step S4 until the solvent in step S1 is completely evaporated to obtain a suspension;

[0013] S6. Filter and wash the suspension to obtain capsule particles, namely the pH-responsive initiator.

[0014] Preferably, in step S1, the shell material is selected from one or more of rosin, PMMA, and polyethylene terephthalate.

[0015] Preferably, in step S1, the mass fraction of the shell material in the oil phase solution is 20% to 50%.

[0016] Preferably, in step S1, the boiling point of the solvent is not higher than 80°C.

[0017] Preferably, in step S1, the solvent is diethyl ether, acetone or tetrahydrofuran.

[0018] Preferably, in step S2, the water-soluble polymer has viscosity in water and is selected from polypropylene alcohol, styrene acrylic and a mixture thereof.

[0019] Preferably, in step S2, the mass fraction of the water-soluble polymer in the water-soluble polymer solution is 7% to 10%.

[0020] Preferably, in step S2, the amount of the water-soluble polymer solution added is 30% to 50% of the mass of the oil phase solution in step S1.

[0021] Preferably, in step S2, the coated small molecule is a persulfate initiator, and the added amount is 30% to 60% of the mass of the shell material.

[0022] Furthermore, in step S2, the coated small molecule is ammonium persulfate, potassium persulfate or sodium persulfate.

[0023] Preferably, in step S3, the emulsification shear rate of the emulsification shearing machine is 2000-5000 rpm, and the emulsification time is 5-10 min.

[0024] Preferably, in step S4, the mass fraction of the water-soluble polymer in the diluted aqueous solution of the water-soluble polymer is 3-5%, the added amount is 150%-250% of the mass of the water-soluble polymer aqueous solution in step S3, and the emulsification time is 5-10 min.

[0025] Preferably, in step S5, the heating temperature is 50-80°C.

[0026] Preferably, in step S6, filtering is performed using a Buchner funnel, and washing is performed using water for 3 to 5 times.

[0027] The pH-responsive initiator prepared by the above method is used to improve the mechanical properties of cement-based materials.

[0028] The application of the pH responsive initiator in cement-based materials is as follows: a mixed solution of the pH responsive initiator and a monomer solution is used as solution A, and a reducing initiator solution is used as solution B, and solution A and solution B are added to the cement-based material at the same time to improve the mechanical properties of the cement-based material; wherein the monomer solution is an acrylamide solution or a sodium acrylate solution, and the amount of the monomer is 1-3% of the total mass of the cementitious material in the cement-based material; and the reducing initiator is an amine initiator, and the amount is 0.2%-0.8% of the monomer mass.

[0029] Preferably, the reductive initiator is tetramethylethylenediamine, ethylenediamine or diethanol monoisopropanolamine.

[0030] Beneficial effects: Since polymerization reactions usually require the simultaneous presence of monomers and initiators, the purpose of controlling the in-situ polymerization reaction time can be achieved by controlling the timing of adding a certain component to the polymer system. Therefore, micro-nano materials that can carry drugs and can be released in a controlled manner meet the requirements for polymerization time control in this system. In the present invention, an alkali-activated capsule sustained-release material is used as a carrier, and an active initiating component is introduced into the sustained-release material so that it can be broken during the hydration process of the cement-based material, thereby initiating polymerization in situ in the cement-based material to achieve the purpose of controlling the polymerization time. Based on coordination, electrostatics, hydrogen bonds, and chemical bond interactions, organic polymers are compounded with CSH gels at the molecular scale, and the sizes and stacking methods of organic polymers and CSH gels are regulated and optimized. The polymer phase size is reduced to a size close to that of the hydration product, and the polymer induces the optimization of the size and orientation of the hydration product, and enhances the interfacial bonding between the hydration products and fills the internal pores, thereby achieving a significant improvement in the mechanical properties of the cement-based material. When the admixture is applied to cement-based materials, it can effectively improve the microstructure of the cement-based materials, compact the pores, and use polymer toughening to give the cement-based materials better flexural properties without significantly reducing the compressive properties of the cement-based materials.

[0031] In this system, at the molecular scale, small monomer molecules can be adsorbed on the surface of cement particles in advance, participate in hydration, and form weak interactions between molecules; at the micrometer scale, the polymer in situ polymerized on the surface of cement hydration product particles can modify the surface of the hydration product, improve its surface chemical environment while improving the interaction between the phases in the interface transition zone, fill the pores between the phases, and increase adhesion; at the macroscopic scale, the polymer can play a filling effect and is used to fill pores and cracks. The uniform dispersion of polymer and cement particles effectively solves the problem of medium phase separation in the polymer / cement system, which can increase the flexural strength of concrete while not reducing the compressive strength. Under the conditions of in-situ polymerization, polymer interpenetrating networks are easier to form, and the polymer / cement composite material model with coupling effect can effectively improve the mechanical properties of concrete.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] (1) The initiator provided by the present invention uses a small molecule monomer rather than a polymer, which has little effect on cement-based materials and does not affect the hydration of cement-based materials while improving the flexural properties.

[0034] (2) The initiator of the present invention has a sustained release effect. In the early stage of hydration, the oxidative initiator is not released. After a period of hydration, that is, after the shell material is dissolved in the alkaline solution for a period of time, the oxidative initiator is released to initiate polymerization, thereby minimizing the effect of the polymer on cement hydration.

[0035] (3) The preparation method provided by the present invention has a wide range of raw material sources, is safe and environmentally friendly, and the preparation process is simple and easy to control. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 is a SEM image of a pH-responsive initiator prepared according to Example 1 of the present invention;

[0037] Figure 2 is a TGA chart of the pH responsive initiator prepared according to Example 1 of the present invention. DETAILED DESCRIPTION

[0038] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments.

[0039] Example 1

[0040] A pH-responsive initiator for improving the mechanical properties of cement-based materials is prepared by the following method:

[0041] (1) Preparation of oil phase solution: Mix 1 part of rosin and 4 parts of ether evenly by weight;

[0042] (2) Preparation of aqueous solution: by weight, 0.5 parts of ammonium persulfate and 2 parts of 10 wt% PVA solution were mixed evenly;

[0043] (3) Pour the aqueous phase solution into the oil phase solution under the action of an emulsifying shearing machine at 3000 rpm and emulsify in an ice water bath for 5 min;

[0044] (4) Add 15 parts by weight of 4 wt % PVA solution to the obtained emulsion and continue emulsification for 5 minutes;

[0045] (5) Heat the solution to 50°C and stir for 4 h until the ether is completely evaporated.

[0046] The above solution was filtered and rinsed with water three times to obtain sample S1.

[0047] Example 2

[0048] A pH-responsive initiator for improving the mechanical properties of cement-based materials is prepared by the following method:

[0049] (1) Preparation of oil phase solution: Mix 4 parts of rosin and 4 parts of ether evenly by weight;

[0050] (2) Preparation of aqueous solution: By weight, 1.2 parts of ammonium persulfate and 2.4 parts of 7 wt % PVA solution were mixed evenly;

[0051] (3) Pour the aqueous phase solution into the oil phase solution under the action of an emulsifying shearing machine at 5000 rpm and emulsify in an ice water bath for 10 min;

[0052] (4) Add 12 parts by weight of 3 wt % PVA solution to the obtained emulsion and continue emulsification for 10 minutes;

[0053] (5) Heat the solution to 80°C and stir for 2 h until the ether is completely evaporated.

[0054] The above solution was filtered and rinsed with clean water 5 times to obtain sample S2.

[0055] Example 3

[0056] A pH-responsive initiator for improving the mechanical properties of cement-based materials is prepared by the following method:

[0057] (1) Preparation of oil phase solution: Mix 1 part of PMMA and 4 parts of acetone evenly by weight;

[0058] (2) Preparation of aqueous solution: by weight, 0.5 parts of potassium persulfate and 2 parts of a mixed solution were mixed evenly, wherein the mixed solution was a 10 wt% PVA and styrene acrylic solution mixed in a weight ratio of 1:1;

[0059] (3) Pour the aqueous phase solution into the oil phase solution under the action of an emulsifying shearing machine at 3000 rpm and emulsify in an ice water bath for 5 min;

[0060] (4) Add 15 parts by weight of 4 wt % PVA solution to the obtained emulsion and continue emulsification for 5 minutes;

[0061] (5) Heat the solution to 50°C and stir for 4 h until the acetone is completely evaporated.

[0062] The above solution was filtered and rinsed with clean water three times to obtain sample S3.

[0063] Example 4

[0064] A pH-responsive initiator for improving the mechanical properties of cement-based materials is prepared by the following method:

[0065] (1) Preparation of oil phase solution: Mix 1 part of polyethylene terephthalate and 4 parts of tetrahydrofuran by weight;

[0066] (2) Preparation of aqueous solution: Mix 0.5 parts of sodium persulfate and 2 parts of 10 wt% styrene acrylic solution evenly by weight;

[0067] (3) Pour the aqueous phase solution into the oil phase solution under the action of an emulsifying shearing machine at 3000 rpm and emulsify in an ice water bath for 5 min;

[0068] (4) Add 15 parts by weight of 4 wt % PVA solution to the obtained emulsion and continue emulsification for 5 minutes;

[0069] (5) Heat the solution to 50°C and stir for 4 h until the tetrahydrofuran is completely evaporated.

[0070] The above solution was filtered and rinsed with clean water three times to obtain sample S4.

[0071] Example 5

[0072] A pH-responsive initiator for improving the mechanical properties of cement-based materials is prepared by the following method:

[0073] (1) Preparation of oil phase solution: Mix 2 parts of rosin and 4 parts of ether evenly by weight;

[0074] (2) Preparation of aqueous solution: By weight, 1.2 parts of ammonium persulfate and 2 parts of 10 wt% PVA solution were mixed evenly;

[0075] (3) Pour the aqueous phase solution into the oil phase solution under the action of an emulsifying shearing machine at 2000 rpm and emulsify in an ice water bath for 10 min;

[0076] (4) Add 23 parts by weight of 5 wt% PVA solution to the obtained emulsion and continue emulsification for 5 minutes;

[0077] (5) Heat the solution to 50°C and stir for 4 h until the ether is completely evaporated.

[0078] The above solution was filtered and rinsed with clean water three times to obtain sample S5.

[0079] Example 6

[0080] A pH-responsive initiator for improving the mechanical properties of cement-based materials is prepared by the following method:

[0081] (1) Preparation of oil phase solution: Mix 2 parts of rosin and 4 parts of ether evenly by weight;

[0082] (2) Preparation of aqueous solution: by weight, 0.5 parts of ammonium persulfate and 3 parts of 10 wt% PVA solution were mixed evenly;

[0083] (3) Pour the aqueous phase solution into the oil phase solution under the action of an emulsifying shearing machine at 3000 rpm and emulsify in an ice water bath for 5 min;

[0084] (4) Add 15 parts by weight of 4 wt % PVA solution to the obtained emulsion and continue emulsification for 5 minutes;

[0085] (5) Heat the solution to 50°C and stir for 4 h until the ether is completely evaporated.

[0086] The above solution was filtered and rinsed with clean water three times to obtain sample S6.

[0087] Cement mortar fluidity test:

[0088] The fluidity of cement mortar was tested in accordance with the national standard GB / T 8077-2012 "Test method for homogeneity of concrete admixtures", using a naphthalene-based high-efficiency water reducer. The comparison results are shown in Table 1. In the fluidity test, no AM monomer was added to the sample.

[0089] Table 1 Comparison of mortar fluidity test

[0090]

[0091] It can be seen from the data in Table 1 that after adding the pH-responsive initiator sustained-release capsules of the present invention, the fluidity of the corresponding cement-based material does not change significantly, which proves that the inorganic admixture has no effect on the working performance of cement.

[0092] The pH-responsive initiator sustained-release capsule material of the present invention is used in cement-based materials, and the specific application is as follows:

[0093] The mortar material ratio shown in Table 2 was adopted, and the sustained-release capsule material provided in the above embodiments was added to prepare the mortar. Specifically, 16.2 g of acrylamide monomer and the sample obtained above were dispersed in 120 g of aqueous solution in different dosages to obtain solution A, and 0.033 g of amine initiator was dispersed in 120 g of water to obtain solution B. When the mortar was stirred and formed, the A and B solutions were blended to replace the water required for the forming to prepare the mortar, and the mortar was cured at room temperature. At the same time, a comparison group was set up, in which the sustained-release capsule obtained above was not added to the comparison group, and only acrylamide monomer and solution B were added.

[0094] Table 2 Mortar mix ratio

[0095]

[0096] The mechanical properties of the mortars at different sustained-release capsule dosages and ages were tested according to the test method (Construction and Building Materials, 2013, 49: 121). The test results are as follows:

[0097] Table 3 Mechanical properties of mortar (dosage based on cement mass)

[0098]

[0099] As can be seen from Table 3, the flexural and compressive strength data of the cement test block added with the sustained-release capsule provided by the present invention at 7d and 28d are significantly improved compared with the reference and blank, and the difference in the effect of different dosages on the mechanical properties is small. Due to the slow setting effect of the monomer, the compressive strength is slightly reduced at 7d. Among them, the flexural strength at 7d can be improved by 24.41%, and the flexural strength at 28d can be improved by 44%.

[0100] These examples prove that the sustained-release capsule material provided by the present invention can be used to enhance the mechanical properties of cement-based materials.

Claims

1. A method for preparing a pH-responsive initiator for improving the mechanical properties of cement-based materials, characterized in that: The steps include: S1. Preparation of oil phase solution: using a polymer that can be hydrolyzed under alkaline conditions as a shell material, dissolving the shell material in a solvent as an oil phase solution; the shell material is selected from one or more of rosin, PMMA, and polyethylene terephthalate, and the mass fraction of the shell material in the oil phase solution is 20% to 50%; S2. Preparation of aqueous solution: mixing a water-soluble polymer aqueous solution and a coated small molecule as an aqueous solution; the coated small molecule is a persulfate initiator, and the addition amount is 30% to 60% of the mass of the shell material; S3. Under the action of the emulsifying shearing machine, the aqueous phase and the oil phase solution are mixed and emulsified to form an emulsion; S4. Adding a diluted aqueous solution of a water-soluble polymer to the emulsion, and continuing emulsification; S5. Heating the emulsion in step S4 until the solvent in step S1 is completely evaporated to obtain a suspension; S6. Filter and wash the suspension to obtain capsule particles, namely the pH-responsive initiator.

2. The method for preparing a pH-responsive initiator for improving the mechanical properties of cement-based materials according to claim 1, characterized in that: In step S2, the water-soluble polymer has viscosity in water and is selected from polypropylene alcohol, styrene acrylic emulsion and a mixture thereof. The mass fraction of the water-soluble polymer in the water-soluble polymer solution is 7% to 10%, and the amount of the water-soluble polymer solution added is 30% to 50% of the mass of the oil phase solution in step S1.

3. The method for preparing a pH-responsive initiator for improving the mechanical properties of cement-based materials according to claim 1, characterized in that: In step S2, the coated small molecule is ammonium persulfate, potassium persulfate or sodium persulfate.

4. The method for preparing a pH-responsive initiator for improving the mechanical properties of cement-based materials according to claim 1, characterized in that: In step S3, the emulsification shear rate of the emulsification shearing machine is 2000-5000 rpm, and the emulsification time is 5-10 min.

5. The method for preparing a pH-responsive initiator for improving the mechanical properties of cement-based materials according to claim 1, characterized in that: In step S4, the mass fraction of the water-soluble polymer in the diluted aqueous solution of the water-soluble polymer is 3-5%, the added amount is 150%-250% of the mass of the water-soluble polymer aqueous solution in step S3, and the emulsification time is 5-10 minutes.

6. A pH-responsive initiator for improving the mechanical properties of cement-based materials prepared by the method of claim 1.

7. Use of the pH-responsive initiator according to claim 6 in cement-based materials, characterized in that: The application method is as follows: a mixed solution of the pH-responsive initiator and the monomer solution is used as solution A, and a reducing initiator solution is used as solution B, and solution A and solution B are simultaneously added to cement-based materials to improve the mechanical properties of cement-based materials; wherein the monomer solution is an acrylamide solution or a sodium acrylate solution, and the amount of the monomer is 1-3% of the total mass of the cementitious material in the cement-based material; and the reducing initiator is an amine initiator, and the amount is 0.2%-0.8% of the mass of the monomer.

8. The use of the pH-responsive initiator in cement-based materials according to claim 7, characterized in that: The reductive initiator is tetramethylethylenediamine, ethylenediamine or diethanol monoisopropanolamine.

Citation Information

Patent Citations

  • Preparation method for silicon dioxide aerogel microsphere coated ammonium persulfate delaying gel-breaking agent

    CN107304356A

  • Method for preparing self-crosslinking composite shell microcapsules

    CN110327857A